Predicting phenotypes from brain connection structure. Issue 3 (9th April 2022) - Guha, Subharup; Jung, Rex; Dunson, David
Abstract: This article focuses on the problem of predicting a response variable based on a network‐valued predictor. Our motivation is the development of interpretable and accurate predictive models for cognitive traits and neuro‐psychiatric disorders based on an individual's brain connection network (connectome). Current methods reduce the complex, high‐dimensional brain network into low‐dimensional pre‐specified features prior to applying standard predictive algorithms. These methods are sensitive to feature choice and inevitably discard important information. Instead, we propose a nonparametric Bayes class of models that utilize the entire adjacency matrix defining brain region connections to adaptively detect predictive algorithms, while maintaining interpretability. The Bayesian Connectomics (BaCon) model class utilizes Poisson–Dirichlet processes to find a lower dimensional, bidirectional (covariate, subject) pattern in the adjacency matrix. The small n, large p problem is transformed into a 'small n, small q ' problem, facilitating an effective stochastic search of the predictors. A spike‐and‐slab prior for the cluster predictors strikes a balance between regression model parsimony and flexibility, resulting in improved inferences and test case predictions. We describe basic properties of the BaCon model and develop efficient algorithms for posterior computation. The resulting methods are found to outperform existing approaches and applied to a creative reasoning dataset.